Transformation of communities’ perceptions towards women’s participation in Uganda’s politics - Mutuuzo, Peace Regis; Makara, Sabiti; Ssali, Sarah (East African Journal of Peace & Human Rights, 2025)
Despite the fact that Uganda reserves 30% of electoral seats for women alongside open seats to promote gender equality in politics, the increase in women’s political representation is largely due to these reserved seats and not success in the open seat contests. This study investigated whether communities’ perceptions have shifted to support equal gender representation in politics. It specifically assessed the local communities’ willingness to vote for a woman competing against a man for an open seat, and the willingness of Members of Parliament (MPs) to support a policy of equal gender representation in politics. The study used a cross-sectional design and employed random sampling techniques to collect both qualitative and quantitative data from 400 respondents across four Ugandan districts: Kasese, Mukono, Jinja, and Arua. It also included 16 gender-segmented focus group discussions and 38 Key Informant Interviews (KIIs). Findings revealed that communities’ perceptions have transformed. For instance, 91.8 per cent of respondents expressed willingness to vote for a woman contesting with a man on an open seat. The main reasons for this willingness were; leadership qualities, ability to represent women's issues, and transparency. However, actual voting patterns did not reflect this willingness. In addition, male MPs expressed unwillingness to support a gender parity policy, citing concerns about losing dominance over women, disruption of the male-led social order, and a belief that women are adequately represented in other sectors. The study recommends amending Articles 79 and 189 of the Ugandan Constitution to guarantee equal gender representation in all elective positions and close the gender gap in politics.